They support, so we talk: the effects of other users on self-disclosure on social networking sites. Issue 3 (14th July 2020) - Lin, Cheng-Yu; Chou, En-Yi; Huang, Heng-Chiang
Abstract : Purpose: Social networking sites (SNSs) have significantly influenced people's lives and changed their behavior. Although previous research has explored self-disclosure in virtual communities, little is known about the impact of other users, particularly their online social support, on self-disclosure. The aim of this study is to explore how online social support dimensions (i.e., emotional, informational, esteem, instrumental and network support) influence people's self-disclosure, which in turn affects their commitment to SNSs. Design/methodology/approach: Based on social exchange theory, this study proposes a research model that explores the role of other users on self-disclosure. This study collects data from a sample of 558 respondents and applies the structural equation modeling technique to test the research model. Findings: The findings show that users are motivated to disclose information and commit to a specific SNS because of the supportive climate. Results also show that self-disclosure mediates the effect of online social support on users' commitment to SNSs. Originality/value: This study focuses on the influence of other users' roles on self-disclosure on SNSs, extending the application of social exchange theory.